THE CURRENT STATUS OF JOB BURNOUT AMONG ONLINE NURSES DELIVERING INTERNET+ HOME CARE SERVICES AND INFLUENCING FACTORS: A CROSS-SECTIONAL STUDY - Yinan Wang (LIFE: International Journal of Health and Life-Sciences, 2025)
Statement of the Problem: Job burnout is common among nurses. Related studies have focused on specialized hospital departments such as intensive care units and emergency rooms. In one form of ‘internet +’ nursing services in China, nurses provide home care at patients' residences. A common model involves part-time clinical nurses from tertiary hospitals delivering these services. However, nurses’ means of coping with work stress and job burnout under this new workload have received little attention. The purpose of this study is to explore the relationship between stress coping styles and job burnout among nurses in China. Methodology: A cross-sectional design was used. From September to November 2024, 287 nurses from seven tertiary hospitals who performed ‘internet +’ services were surveyed. The relationship between stress coping styles and job burnout levels was analysed using the Simplified Coping Style Questionnaire (SCSQ) and the Nurse Burnout Scale (NBS). Findings: Nurses reported low job burnout scores (122.29±28.46; ranging 57~228), indicating either extremely mild or no job burnout. Specifically, positive coping styles were negatively correlated with total job burnout scores (r=-0.415, p < 0.01), whereas negative coping styles were positively correlated with total scores (r=0.174, p < 0.01).Factors that influence job burnout include nurses’ clinical department, educational background, marital status, average monthly income from ‘internet +’ nursing services over the past three months, and coping styles. Married nurses with higher academic qualifications working in outpatient and emergency care departments experienced notably lower levels of job burnout. The stress coping styles of nurses who provide ‘internet +’ nursing services in tertiary hospitals and job burnout levels are significantly correlated. Nursing managers should focus on stress coping strategies and job burnout awareness to create environments in which positive coping strategies are encouraged.